Volatile biogenic organic compounds: state of the art on sampling methodologies and quantification of their gas emissions - Mora-Barrantes, Jose Carlos (2024)
Volatile Organic Biogenic Compounds (VOBC) are produced by a wide variety of sources in terrestrial ecosystems (flowers, stems, trunks, roots, leaf litter, among others). Among the different types of VOBC are compounds such as terpenoids, oxygenated compounds, alkanes, alkynes, organic halides, among others. The current research provides a description of the state of the art regarding the various methodologies applied for the sampling and quantification of biogenic volatile organic compounds (BVOCs). The present project evaluated 20 different studies in which BVOCs were analysed in various environments (forests, cities, specific plants, agricultural areas, flowers, pathogens, Mediterranean ecosystems, among others). The results indicate that there are several techniques used in the quantification of BVOCs, with the two analytical techniques most commonly used being gas chromatography-based techniques, such as gas chromatography-mass spectrometry (GC-MS), gas chromatography with flame ionization detection (GC-FID), and thermal desorption-gas chromatography-mass spectrometry (TD-GC-MS); and techniques based on soft chemical ionization mass spectrometry, such as selected ion flow tube mass spectrometry (SIFT-MS) and proton transfer reaction mass spectrometry (PTR-MS). It is concluded that the choice of suitable analytical techniques for the analysis of BVOCs depends on the specific objectives of the study, sample characteristics, and required sensitivity. Gas chromatography-based techniques, such as GC-MS, GC-FID, and TD-GC-MS, are used for the precise identification and quantification of BVOCs in complex samples, while soft chemical ionization mass spectrometry techniques, such as SIFT-MS and PTR-MS, are employed in situations that require real-time response and high sensitivity.